Produksi Gas Hidrogen dari Air Laut Menggunakan Proses Photovoltaic-Electrolysis dengan Katalis H2SO4 - Lukman Hakim; Elma Agustina Berutu; Ratna Sari; Ratni Dewi (Jurnal Serambi Engineering, 2023)
AbstractHydrogen is a new and renewable energy that has advantages over other energies. Among the hydrogen gas production methods that have the potential to be developed is seawater electrolysis, which is an abundant source. The electrolysis method uses a Direct Current (DC) electric current source. In this study, DC electric current was used from the results of solar panels (photovoltaic) with a volume of seawater as an electrolyte solution of 3500 ml. The electrolysis process times were 15, 30, 45, and 60 minutes using graphite electrodes with variations in voltages of 5, 10, 15 and 20 volts and H2SO4 catalyst concentrations of 0.1M, 0.25M, 0.5M and 0.75M at ambient conditions and 1 atm. The study results showed that the voltage and catalyst concentration of H2SO4 showed the effect of the formation of hydrogen gas. Where the effect of the loading voltage is reversed with the catalyst concentration of H2SO4. The higher voltage, the flow rate of the hydrogen gas produced also increases and the higher the concentration of H2SO4 catalyst used, lower the flow rate of the hydrogen gas produced. Based on the research results, the highest hydrogen gas flow rate was obtained at a catalyst concentration of 0.1M H2SO4, at a voltage of 20 volts with a flow time of 60 minutes, a flow rate of 20.5 ml/minute and in seawater electrolysis using H2SO4 catalyst did not produce NaOCl as a byproduct.Keywords: electrolysis, energy, graphite, hydrogen, catalyst